2017
DOI: 10.1002/hed.24975
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic spread from squamous cell carcinoma of the hypopharynx to the totally implantable venous access port insertion site: Case report and review of literature

Abstract: We present a novel case of metastasis over the totally implantable venous access port implanted in a patient with a hypopharyngeal tumor. We also reviewed relevant literature comparing the data from percutaneous endoscopic gastrostomy (PEG) tube site metastasis with our patient and other similar case reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Mangla et al reported on the first patient with squamous cell carcinoma of the hypopharynx who developed tumour seeding not only at the insertion site of the TIVAP but also along the tunnel tract of the catheter itself. 19 Of the 200 children selected for this study that were implanted with TIVAPs in our department, eight were diagnosed with CRBSIs, and the infection rate was 3%, which is consistent with the findings from the Infectious Diseases Society of America mentioned above ( Table 3 ).…”
Section: Discussionsupporting
confidence: 88%
“…Mangla et al reported on the first patient with squamous cell carcinoma of the hypopharynx who developed tumour seeding not only at the insertion site of the TIVAP but also along the tunnel tract of the catheter itself. 19 Of the 200 children selected for this study that were implanted with TIVAPs in our department, eight were diagnosed with CRBSIs, and the infection rate was 3%, which is consistent with the findings from the Infectious Diseases Society of America mentioned above ( Table 3 ).…”
Section: Discussionsupporting
confidence: 88%
“…There are only a few reports of cancer metastasis around TIVAP insertion sites (Table 1). [1][2][3] The literature indicates that head-andneck, hematologic and intrathoracic malignancies appear to be the most common cause, with squamous cell carcinoma being the most common histologic type. Aggressive, progressive or poorly differentiated tumours are more likely to be associated with tumour dissemination to the insertion site than localised or welldifferentiated tumours.…”
Section: Subcutaneous Metastasis At the Totally Implantable Venous Ac...mentioning
confidence: 99%